Experimental investigation of infill parameters influence on compressive strength-to-mass ratio of PLA 3D printed part / The Jaya Suteja - Suteja, The Jaya (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
An infill pattern can be implemented in manufacturing a porous component using 3D Printing technology to reduce the mass of the printed part. The use of an infill pattern and infill angle affects the structure of the printed part. This research aims to investigate the effect of various infill patterns and angles on the compressive strength-to-mass ratio of components manufactured by 3D Printing. This research implements a General Linear Model analysis with two replications. Seventy-two compressive test specimens, according to ASTM D695, are printed and tested for compression. The experiment results show that the type of infill pattern has a significant effect on the mass. However, the mass is not significantly influenced by the infill angle. In addition, the infill pattern type and the infill angle significantly influence the compressive strength of the specimen. Then, the compressive strength-to-mass ratio is significantly affected by the infill patterns and angles. The results indicate that a part using the Honeycomb infill pattern type gains the highest compressive strength-to-mass ratio compared to other infill patterns. On the opposite, the infill pattern that creates the lowest compressive strength-to-mass ratio compared to other infill patterns is the Archimedean chords type. The use of a 45° infill angle causes the lowest compressive strength-to-mass ratio compared to other infill angles. Using a 90° infill angle causes the highest compressive strength-to-mass ratio compared to other infill angles.